Intrinsic and extrinsic inhomogeneities in mixed-valence manganites - Belevtsev, B.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
It is suggested that extrinsic inhomogeneities in mixed-valence manganites deserve more attention and they should be taken into account on equal footing with hypothetical phase separation while examinating experimental data and developing the theoretical models of the influence of stoichiometric and other types of inhomogeneities on the properties of these and other transition-metal oxides.